2017
DOI: 10.1186/s12967-017-1277-6
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte depletion from bone marrow: performance evaluation after 50 clinical-scale depletions with Spectra Optia BMC

Abstract: BackgroundRed blood cell (RBC) depletion is a standard graft manipulation technique for ABO-incompatible bone marrow (BM) transplants. The BM processing module for Spectra Optia, “BMC”, was previously introduced. We here report the largest series to date of routine quality data after performing 50 clinical-scale RBC-depletions.MethodsFifty successive RBC-depletions from autologous (n = 5) and allogeneic (n = 45) BM transplants were performed with the Spectra Optia BMC apheresis suite. Product quality was asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
12
0
2
Order By: Relevance
“…Most common methods of RBC removal are sedimentation under gravity, after the addition of hydroxyethyl starch (HES), separation on a Ficoll gradient and processing by a blood cell separator. The blood cell separator within an automated system is progressively becoming more and more common in the most recent practice, allowing efficient RBC removal and limited cell loss [4,6,7].…”
Section: Major Incompatibilitymentioning
confidence: 99%
“…Most common methods of RBC removal are sedimentation under gravity, after the addition of hydroxyethyl starch (HES), separation on a Ficoll gradient and processing by a blood cell separator. The blood cell separator within an automated system is progressively becoming more and more common in the most recent practice, allowing efficient RBC removal and limited cell loss [4,6,7].…”
Section: Major Incompatibilitymentioning
confidence: 99%
“…Different manual or semiautomated techniques are used for RBC depletion before ABO‐incompatible transplantation or cryopreservation; these include gravity sedimentation with hydroxyethyl starch (HES) 7–9 or dextran, 10 the addition of third‐party RBCs to buffy coat, 11,12 and Ficoll‐Hypaque used together with blood cell separators 2,13–15 . Bone marrow processing using cell separation devices has recently been developed 16–23 . COBE Spectra (COBE BCT, Lakewood, CO, USA) is a continuous flow cell separator that isolates cells through centrifugation and buffy layer formation under the manual interface management.…”
Section: Introductionmentioning
confidence: 99%
“…These apheresis devices are used to effectively remove RBCs from large bone marrow volumes with a high rate of hematopoietic cell subpopulation recovery. [18][19][20][21][22][23] However, low RBC volume is an obstacle to the processing of small-volume bone marrow collected from or for light pediatric recipients. Previous studies reported processing of low-volume bone marrow using other cell separator systems with thirdparty RBC-manipulation or ficoll density centrifugation.…”
Section: Introductionmentioning
confidence: 99%
“…Seit den 1990er-Jahren besitzt die allogene Blutstammzelltransplantation einen international anerkannten Stellenwert in der Therapie einer Vielzahl von hämatologischen und lymphatischen Neoplasien, aber auch bei angeborenen und erworbenen nichtmalignen Erkrankungen der Blutbildung und des Immunsystems. [6,7]. Die in einigen Zentren praktizierte gezielte Fehltransfusion major-inkompatibler Erythrozytenkonzentrate zur Adsorption der gegen die Spenderblutgruppe gerichteten Isoagglutinine des Empfängers ist ebenfalls effektiv, sofern der Isoagglutinintiter des Empfängers einen Wert von 32 nicht überschreitet [8,9].…”
Section: Introductionunclassified